The competent approach in the professional training of future elementary school teachers (Pedagogy of Higher and Secondary Education, 2012)
Kazanghy I. The competent approach in the professional training of future elementary school teachers.The article is devoted to the meaning of a competent approach in the future specialists’ training under the conditions of Euro Integration process; the components of school teachers’ professional educative competence are described here.
Keywords: Euro Integration; competent approach; educative competence; readiness to the educational work